MEASUREMENT OF STUDENT MATHEMATICS LEARNING OUTCOMES BASED ONLINE: A SYSTEMATIC LITERATURE REVIEW (International Conference on Social and Islamic Studies, 2021)
Research on the development of e-learning learning media has grown rapidly during the COVID-19 pandemic, as has the development of valid mathematics learning outcomes tests. This article aims to review the types of platforms and forms of students' mathematics learning outcomes in online learning. It is a Systematic Literature Review research that examines articles published in 2020-2021, specifically related to the online platforms used to measure students' mathematics learning outcomes and the forms of the tests used. The conclusion of this study is that the types of platforms used include Google Form, Quizizz, Geogebra for Smartphone, Kahoot, Hot Potatoes, and Ispring Suite, while the forms of the tests are multiple choice, true-false questions, brief filled-in questions, and essay test. Based on the results of this study, it is recommended to choose a platform that is in accordance with the forms of the questions used.